PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM PEMENUHAN KEBUTUHAN DASAR PENGUNGSI DI KOTA KUPANG DITINJAU DARI PERATURAN PRESIDEN NOMOR 125 TAHUN 2016 - Regaletha, Redemptus D. L.; Tadeus, D. W.; Bunga, Gerald Aldytia; Ch Likadja, Jeffry A. (UNES Law Review, 2023)
One country that is often a transit country for people seeking asylum elsewhere is Indonesia. Due to its location, Indonesia can become an illicit trade corridor and a stopover for people seeking asylum in Australia. As the influx of these refugees is deemed to pose a danger to national security and resilience, these illegal arrivals are certainly bad for Indonesia. Every person entering or leaving Indonesia is required by law to have a valid travel document. Indonesian laws and regulations governing the treatment of international refugees are inadequate. The purpose of this study is to analyse the role of IOM in fulfilling the basic needs of refugees in Kupang City in terms of Presidential Regulation Number 125 of 2016 concerning the handling of refugees from abroad". Normative-Empirical (applied) legal research. Researchers apply qualitative data analysis methods. The approaches used in this legal research are statutory approach, historical approach and conceptual approach. The result of this research is that IOM in Indonesia has supported the Indonesian government in its efforts to overcome migration problems, both domestic and international. In Indonesia, IOM fulfils its policies regarding protection and a rights-based approach, by assisting migrants and refugees directly in accordance with the references or referrals given by the Indonesian Government to IOM. As a country that did not ratify the 1951 Refugee Convention, Indonesia still respects the rights of refugees including the right to fulfil basic needs for refugees in Kupang City. As referred to in Presidential Regulation No. 125 of 2016 concerning the handling of refugees from abroad.